Post-Adoption Beliefs Influencing Continued Participation in Virtual Communities (Global Journal of Human-Social Science, 2016)
This study aims to investigate what motivates individuals to continue to participate in virtual communities. A comprehensive model that incorporates the antecedents of individuals' behavioral intention to continued participation in virtual communities is proposed and empirically tested. The data for this study were collected through a Web survey and analyzed using structural equation modeling. The results indicate that attitude toward participating in virtual communities is a significant predictor of continuance intention. The strongest influence on attitude toward participation was found for perceived enjoyment. Perceived usefulness and subjective norm were found to have significant positive influences on attitude toward participation. The implications of the results of this study are expected to contribute to identifying key predictors of individuals' continued intentions to participate in virtual communities and provide insights into effective strategies to vitalize virtual communities in the post-adoption stage.
Keywords: virtual community; continued participation; perceived usefulness; enjoyment; social presence; subjective norm